Reinforced concrete mechanics and design - MacGregor, James G. (James Grierson) 1934- (Prentice Hall, 1997)
The theory of reinforced concrete design is presented as a direct application of the laws of statics and behavior of reinforced concrete. This book emphasizes that a successful design must not only satisfy the design equations, but practical construction aspects as well. Covering basic undergraduate level concepts and more advanced topics, this book includes detailed treatments of flexure, shear, development and columns at a level suitable for undergraduate use, as well as the more difficult areas of strain compatibility solutions of beams, P-[Delta] analyses of frames, strut-and-tie models, and design for earthquake resistance. The numerous examples are all worked out completely, step-by-step.